Magnetic resonance imaging based coracoid morphology and its associations with subscapularis tears: a new index. (May 2019) - Watson, Adam C.; Jamieson, Richard P.; Mattin, Andrew C.; Page, Richard S.
Background: We aimed to assess the validity of magnetic resonance imaging (MRI) in assessing the subcorocoid space and determine the validity of novel sagittal plane subcorocoid space measurements. Methods: We assessed 33 arthroscopically proven subscapularis tears with MRIs compared to 33 (instability) controls with normal subscapularis tendons. Three examiners analyzed MRIs for seven static indices of corocoid morphology, in axial and sagittal planes. We explored reviewer variation using intraclass correlation coefficients (ICC) and differences between the two groups was explored using t -tests. Results: Groups were similar in characteristics but different in age (cases = 53, controls = 23). ICC showed good (2/7) or excellent (5/7) reliability. Small differences(<1.6 mm) were identified between subscapularis tears and controls in coraco–humeral distance, in axial ( p = 0.092) and sagittal planes ( p = 0.045). There were statistically significant differences between groups when analyzing the angular projection of the coracoid from the glenoid, in both sagittal ( p < 0.0001) and axial planes ( p = 0.045). Conclusions: Acute inferior angulation of the corocoid in the sagittal plane may be associated with subscapularis tears. Static indices are measured within the scapula and not affected by arm position. MRI reliably provided a platform to assess the coracoid. Based on this, we currently consider corocoplasty in patients with subscapularis tears and a sagittal coroco–glenoid angle <60 o to reduce potential impingement.